2011
DOI: 10.1177/0954008311428531
|View full text |Cite
|
Sign up to set email alerts
|

Chelating and biological properties of an azo polymer resin: synthesis, characterization and its application

Abstract: The polymeric ligand (resin) was prepared from 1-(4-hydroxyphenylazo)-2-naphthol (4HPA2N-F) with formaldehyde in the presence of oxalic acid as a catalyst. Poly (4HPA2N-F) was characterized by Fourier transform infrared and 1 H-NMR spectroscopic techniques. The molecular weight of the polymer was determined by gel permeation chromatography. Polychelates were obtained when the dimethylformamide solution of the polymer containing a few drops of ammonium hydroxide was treated with a aqueous solution of Cu(II)/Ni(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Also, the strong interaction between Cu(II) and with N and O donor atoms increased the lipophilic nature and hence increased the activity of compounds towards such microbes. Finally, we concluded that the results obtained in this work showed promised antimicrobial efficiency for the synthesized copper complexes in comparison with others reported in literature 65,66 …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Also, the strong interaction between Cu(II) and with N and O donor atoms increased the lipophilic nature and hence increased the activity of compounds towards such microbes. Finally, we concluded that the results obtained in this work showed promised antimicrobial efficiency for the synthesized copper complexes in comparison with others reported in literature 65,66 …”
Section: Resultssupporting
confidence: 84%
“…Finally, we concluded that the results obtained in this work showed promised antimicrobial efficiency for the synthesized copper complexes in comparison with others reported in literature. 65,66 T A B L E 4 Some calculated energetic properties of PL1, PL2, and their complexes by the DFT method.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…A wide variety of adsorbents like metal oxides [16], activated carbon [17,18], biomass [19,20], polymer, nanosilicates, nanoferrites, resins etc. were extensively used [21][22][23][24][25][26][27]. Polymer-based adsorbents are used worldwide for remediation of wastewater due to their high stability, porosity and large adsorption capacities [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to develop environmental friendly and also low cost process for detecting heavy metals and also dyes in industrial effluents. Heavy metal ions and dyes can be removed from aqueous solutions via modified polymeric materials through reactive functional groups on their surfaces (Roper and Lightfoot, 1995;Chen et al, 2004;Vieira and Beppu, 2005;Chen et al, 2007;Vieira et al, 2007;Niu et al, 2010;Sasidaran et al, 2011;Salehi et al, 2012;. Hence, based on both the environmental and the economical points of view the use of lowcost agricultural by-products has also become a main research focus (Kumar et al, 1987;Babel and Kurniawan, 2003;Wan Ngah and Hanafiah, 2008).…”
Section: Introductionmentioning
confidence: 96%